Gender Differences in the Social Function of Healthy Aging among Older Koreans - Jung, SuJung (Chonnam Research Institute of Nursing Science, 2022)
Purpose: This study aimed to identify gender differences in the social function of healthy aging among older South Koreans. Methods: This study applied a cross-sectional design using secondary data (Survey on the Welfare and Living Conditions of the Elderly in Seoul, 2018), and 3,034 older adults (men=1,420; women=1,614) were sampled. I used multiple regression analysis to identify the factors related to the social function of healthy aging by gender. Results: The study’s findings indicated that women tended to have a poorer socioeconomic and health-related status than men. In addition, women were frailer than men in social health. Moreover, there were significant gender differences in physical and mental health-related functions, in which women fared worse than men. As for the gender-related factors of healthy aging, there was a relationship between the lifestyle factors (frequency of drinking and exercise) and the social function of healthy aging among women. Conclusion: Results of this study revealed the importance of evaluating the social function of healthy aging among older adults by gender to develop appropriate interventions. KCI Citation Count: 0